The pity of war - Ferguson, Niall (Penguin Books, 1998)
The First World War killed around eight million men and bled Europe dry. In this book the author asks: was the sacrifice worth it? Was it all really an inevitable cataclysm and were the Germans a genuine threat? Was the war, as is often asserted, greeted with popular enthusiasm? Why did men keep on fighting when conditions were so wretched?